Efek Antimikroba Capsaicin - Carlos Taolini (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Capsaicin (8-methyl-N-vanillyl-6-nonenamide) is an active component of the Capsicum plant (chili), which is grown as food and for medicinal purposes since ancient times, and is responsible for the spiciness of the fruit. Capsaicin and related compounds (called capsaicinoids) are secondary metabolites of chili which play an important role in plant defense, possibly as an antidote to animals. In addition, there are several pharmacological and physiological properties (pain relief, cancer prevention, beneficial cardiovascular effects, and digestive effects. Capsaicin is an organic compound with a group of alkaloids available in large quantities in fruits from various chilies. Capsaicin has an impact on thermoregulation and metabolism. adipose tissue and is characterized by antioxidant, hypotensive and anticancer effects In general, capsaicinoids inhibit bacterial growth and metabolism, so this compound is also indicated to inhibit the process of biogas production at certain concentrations through the mechanism of bacterial membrane destruction